Life-Cycle Cost Analysis Comparison on Power Generation Based on Natural Gas and Photovoltaic Modules - Iskandar Fitri, Muhammad Affif (Universiti Teknologi PETRONAS, 2020)
Currently, our only method of transferring energy is by using the power of electricity. Different types of energy or methods are used to produce electricity which is later transferred by cable. These methods can be categorized into two types, Non-renewable and renewable energy. With many different methods that can be used, a method must be used to determine the best alternative. Life Cycle-Cost Analysis (LCCA) is a tool that we can use to determine the total cost of an operation or project. It is especially important when the need to compare a product or project that will produce the same performance but different initial and Operating and Maintenance (O&M) cost. From these comparisons, we can determine whether the project is cost-effective or financially feasible.